Unraveling the reaction mechanism of selective C9 monomeric phenols formation from lignin using Pd-Al2O3-activated biochar catalyst. (January 2022) - Gurrala, L.; Kumar, M.M.; Yerrayya, Attada; Kandasamy, Prabu; Castaño, Pedro; Raja, T.; Pilloni, Giovanni; Paek, C.; Vinu, R.
Graphical abstract: Highlights: High selectivity to C9 alkyl guaiacols (51%) was obtained using Pd-Al2 O3 /activated biochar. Pd 0 catalyzes hydrogenation of Cα =Cβ and Al catalyzes dehydroxylation of Cγ −OH. 4-Propyl guaiacol was obtained at 38% selectivity at 240 °C, 3 MPa H2, and 3 h. Coniferyl alcohol was used as a model compound to probe surface reaction chemistry. Propyl guaiacol formation mechanism is elucidated using DFT calculations. Abstract: The conversion of biomass-derived lignin to valuable monomeric phenols at high selectivity is of paramount importance for sustainable biorefineries. In this study, a novel Pd-Al2 O3 supported on activated biochar catalyst is developed for lignin hydrogenolysis. The catalyst characterization revealed that the (1 1 1) planes of both of Pd 0 and Al2 O3 were exposed to the surface. The maximum lignin conversion of 70.4% along with high liquid yield (∼57 wt%) was obtained at 240 °C, 3 h and 3 MPa H2 pressure. The total monomeric phenols yield in the liquid was 51.6 wt%, out of which C9 monomeric guaiacols constituted ∼ 30.0 wt% with 38.0% selectivity to 4-propyl guaiacol. Using the reaction intermediate, coniferyl alcohol, chemoselective hydrogenation of Cα =Cβ is proved to occur over the Pd site, while dehydroxylation of Cγ –OH is shown to occur over the alumina site. An impressive carbon atom economy of 60% was achieved for the production of monomeric phenols.